Allelopathic effects on vegetative propagation, physiological-biochemical characteristic of Alternanthera philoxeroides (Mart.) Griseb from Cinnamomum camphora (L.) Presl. - Xiaxia Wang; Haixia Wang; Yanlei Zhang; Yan Li; Qi Jia; Ziyi Wang; Juan Sun (Ecotoxicology and Environmental Safety)
Alternanthera philoxeroides (Mart.) Griseb is a well-known invasive plant species worldwide. Cinnamomum camphora (L.) Presl. is a plant species that is rich in allelopathic substances which can impede the growth of many other plants. In this study, the allelopathic effects of C. camphora on the growth and development, and physiological-biochemical characteristics of A. philoxeroides were investigated. The findings revealed that the leaves of C. camphora exhibited the capability to suppress the asexual reproduction of A. philoxeroides. The addition of C. camphora leaves resulted in inhibition of the fresh weight, stem length, and stem node number of A. philoxeroides new stems, with the strength of inhibition increasing in proportion to the quantity of C. camphora leaves added. Furthermore, the inhibitory effect of C. camphora leaves on A. philoxeroides was significantly amplified under high temperatures (≥ 30°C). Two allelochemicals had strong inhibitory effects on the vegetative reproduction of A. philoxeroides. The inhibition intensities were all up to 100 % on stem vegetative propagation, were 90.40 % and 100 % on root vegetative propagation from camphor and linalool, respectively. Physiological-biochemical analyses of roots indicated that the two allelochemicals promoted the accumulation of hydrogen peroxide and MDA, disrupting the balance of antioxidant enzyme systems. The two allelochemicals had a strong inhibitory effect on CAT activity and a strong promoting effect on POD activity. The effect on SOD activity was greatly affected by the type and concentration of allelochemicals. Moreover, the two allelochemicals significantly inhibited the accumulation of osmotic regulating substance. The contents of soluble sugar, soluble protein, and proline were significantly down-regulated. In summary, the allelochemicals from C. camphora induced damage to biological membranes, disrupting antioxidant enzyme systems and inhibiting osmoregulation. This resulted in the retardation of growth, development, and potential mortality of A. philoxeroides. These findings would contribute to the knowledge base for A. philoxeroides prevention and control, and enrich the understanding of C. camphora allelopathic substances.